Pengembangan Formulasi Pasta Antiinflamasi Piroksikam Berbasis Ampas Tahu dalam Pemanfaatan Limbah Tahu Di Purwokerto - Nita Triana Sari; Putri Dewi Riayah; Nabila Fasya; Ainul Mardziyati A; Namira Fadhilah B; Nuryanti Nuryanti (Fakultas Farmasi Universitas Pancasila, 2017)
The soybean curd residue is the waste product of soybean. It has potential for being excipients in pharmaceutical preparations because of its high carbohydrate element. This study aims to evaluate the soybean curd residue as excipients of piroxicam antiinfl ammatory paste. The excipient of soybean curd residue is made by isolating it with 0.1% KOH, then being characterized by physical, chemical, and functional test after becoming starch. It was prepared in piroxicam antiinfl ammatory paste preparations with ratio of soybean curd residue starch and manihot strach are F1 (0:0.25), F2 (0.25:0), F3 (1.25:1.25), F4 (1.5:1), and F5 (1:1.5). The result of physical and freeze-thaw stability test were analyzed descriptively. The data of viscosity, stickiness, and spreading power test were analyzed using one-way ANOVA. Soybean curd residue starch’s physic is slightly coarse, cubic-shapes powder, uneven surface and nonporous, slightly hygroscopic, and brownish-white. It has distinctive odor and has no taste. Chemical test showed that it contained carbohydrate and had pH 4.9. Functional test showed on average 15% it has viscosity 1959 cps, fl ow time 6.7 seconds and still angle 39.2o. Results of physical and stability tests showed that F3 were the best piroxicam antiinfl ammatory paste formula.